EFFICACY OF HMG-CoA REDUCTASE INHIBITORS IN COVID-19 PATIENTS MORTALITY RATE: A META-ANALYSES OF RANDOMIZED CONTROL TRIALS - Mohammadreza Shafiei; Mohammadamin Keykhah (Journal of Global Antimicrobial Resistance, 2024)
AIM: This study aims to evaluate the efficacy of HMG-CoA reductase inhibitors in the mortality of patients with Covid-19 BACKGROUND: The sudden emergence of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in 2019 sparked a pandemic of coronavirus disease 2019 (COVID-19), leading to the pressing global health crisis and unprecedented challenges to healthcare systems and scientific communities. The benefit of HMG-CoA reductase inhibitors usage is under debate. METHODS: A comprehensive literature search in Medline, Cochrane, and ClinicalTrial.gov databases was conducted up to May 2024. A systematic review and meta-analysis of included studies were applied using PRISMA guidelines. RESULTS: Our search reached 6 RCTs comprising 2022 patients, including 823 intervention and 1199 placebo groups. Our analysis revealed that statin use slightly reduced the mortality rate (RR 0.95; 95% CI 0.82-1.09; I2 =0%). There was no significant difference in the dosage of the administered statin in the subgroup meta-analysis. CONCLUSIONS: Our study demonstrated that there is no significant difference in the mortality rate between patients receiving HMG-CoA reductase inhibitors and patients with no intervention (placebo-receiving).